Non-invasive cell counting of adherent, suspended and encapsulated mammalian cells using optical density - Ayesha Aijaz; Dylan Trawinski; Scott McKirgan; Biju Parekkadan (BioTechniques)
In situ measurement to determine mammalian cell number in a non-invasive, non-destructive and reagent-free manner is needed to enable continuous cell manufacturing. An analytical method is presented for non-invasive cell counting by conducting multiwavelength spectral analysis of mammalian cells achieving a minimal detectable cell count of 62,500 at 295 nm. Light absorbance was insensitive to culture volume, giving an absolute cell count rather than a concentration. The activation state of cells was also considered. The study was extended to quantification within polymeric microcapsules as an advanced substrate for mammalian cell growth in bioreactor formats and resulted in an offset directly correlating with the absorbance maxima of the polymer. These studies provide feasibility for optical density as a simple end point to indirectly quantify mammalian cell number for continuous monitoring of cell cultures.